PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA CRF150L - Sakti, Putra Arjuna Jawara (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to analyze the effect of product quality, price and brand image on purchasing decisions for Honda CRF150L. In the Nganjuk Cracker Community. This study uses a quantitative approach with causality research methods. The population is all members of the Honda CRF150L Motorcycle Nganjuk Craker Community, totaling 130 people. The sample obtained amounted to 40 respondents and by using a simple random sampling technique. The data collection tool uses a questionnaire. The data analysis in this used technique is multiple linear regression analysis with the help of spssv.25 software. The results obtained in this study are product quality, price and brand image partially or simultaneously have a significant effect on purchasing decisions for Honda CRF150L at the Nganjuk Craker Community